If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 3x = 15 + 8x Solving 2 + 3x = 15 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 2 + 3x + -8x = 15 + 8x + -8x Combine like terms: 3x + -8x = -5x 2 + -5x = 15 + 8x + -8x Combine like terms: 8x + -8x = 0 2 + -5x = 15 + 0 2 + -5x = 15 Add '-2' to each side of the equation. 2 + -2 + -5x = 15 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = 15 + -2 -5x = 15 + -2 Combine like terms: 15 + -2 = 13 -5x = 13 Divide each side by '-5'. x = -2.6 Simplifying x = -2.6
| 5.9x+4.55(3x)=469.2 | | 4.4(1350-x)+2.3x=4932 | | 13=v/4-3 | | 5.4x+9.3x(4)=1405.8 | | 5.4x+9.3(4)=1405.8 | | 5.4(160-x)+4.3x=791.4 | | 6(x-1)=6 | | 5x+16=8x-14 | | 7=5b | | 25z^2-4=0 | | 5/-8+(-1/-6)-(2/-3) | | 3x-3=4+5x | | 68=5.5(h-5) | | 2w-2=25-3w | | n-4=-3(2+n) | | (x/6)+(x/3) | | k-17=-(17-k) | | (2x^2-15x-15)/(2x+3) | | -21/25y | | y-11=2(x-4) | | y-13=6(x-1) | | (x/4)*3=225 | | y-11=5(x-4) | | 3/2a+5/3a-13/6a-2/3=5/6 | | 5(r+6)=-5(r+-4) | | -31=3x+9-8 | | 0.3(y-2)=0.4(1+y) | | 20=2y-16 | | 78x^2=x-7 | | 5.7x=49.59 | | (x+3)(x-7)=(2x+5)(x-7) | | X/4=225 |